Historical and sociological stages of the transformation of the Belarusian family - Bobrova, Anastacia G. (Journal of the Belarusian State University. Sociology, 2023)
The article considers the evolution of the family as a social institution through the prism of system-forming features. The transformation of the family is closely connected with demographic security and represents a change in the structure and functions of the family institution due to the emergence of new values and weakening of old ones. Five main stages of changes in the structure of the Belarusian family with a linkage to the trends of demographic development are highlighted. The point of no return to a multi-generational rural family with many children is defined. The role of state institutions in strengthening the institution of family and supporting motherhood is emphasised. The risk of reducing the function of caring for offspring as fundamental to the preservation of the family as a social institution and, most importantly, the risk of reducing the need for children was revealed. Under conditions of high mortality, low birth rate does not allow to ensure demographic security. At the same time, the strengthening of intergenerational ties, further development of responsible fatherhood and parenthood in general, allows us to talk about the modernisation of the family, the expansion of its concept and functions.
Keywords: family structure; family transformation; marriage rate; divorce rate